Common Fixed Points of Two G-Nonexpansive Mappings via a Faster Iteration Procedure. (21st April 2021) - Khatoon, Sabiya; Uddin, Izhar; Ali, Javid; George, Reny
Abstract : In this work, we study the convergence of a new faster iteration in which two G -nonexpansive mappings are involved in the setting of uniformly convex Banach spaces with a directed graph. Moreover, by constructing a numerical example, we show the fastness of our iteration procedure over other existing iteration procedures in the literature.